The incidence of consecutive manifestations in Von Hippel-Lindau disease - van der Horst-Schrivers, Anouk N. A.; Sluiter, Wim J.; Kruizinga, Roeliene C.; van Leeuwaarde, Rachel S.; Giles, Rachel; Olderode-Berends, Maran J. W.; Links, Thera P. (Familial cancer, 2019)
Von Hippel-Lindau (VHL) disease is an autosomal dominant rare tumor syndrome characterized by high penetrance. VHL mutation carriers develop numerous manifestations in multiple organs during life. The natural course of development of new and growth of existing VHL-related manifestations is still unclear. In this study we aimed to gain insight into the development of subsequent manifestations in VHL disease. We retrospectively scored each new VHL-related manifestation as detected by standard follow-up (retina, central nervous system, kidneys and pancreas, excluding adrenal and endolymfatic sac manifestations) in 75 VHL mutation carriers. The Kaplan–Meier method was used to plot the cumulative proportions of all consecutive manifestations in each organ against age. The cumulative average number of manifestations in all organs during life was calculated by summating these cumulative proportions. Poisson model parameters were used to calculate average time to the detection of consecutive VHL manifestations in each organ. Consecutive VHL-related kidney and retina manifestations during life occur linearly according to Poisson distribution model. The total number of VHL manifestations rises linearly, with an average of seven VHL-related lesions at age 60 years. The incidence of consecutive VHL-related manifestations is constant during life in VHL mutation carriers. Our data is consistent with the notion that somatic inactivation of the remaining allele (Knudson’s “two-hit” hypothesis) is the determining factor in developing new VHL-related manifestations.